2021
DOI: 10.51470/plantarchives.2021.v21.no1.098
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF SALT (NaCl) ON PHOTOSYNTHESIS AND CARBOHYDRATES IN LEAVES OF TWO RAGI (ELEUSINE CORACANA (L.) GAERTN) VARIETIES

Abstract: Salinity is one of the most widespread environmental threats to global crop production, especially in arid and semi-arid regions. Photosynthesis and carbohydrates were determined in two ragi (Eleusine coracana (L.) Gaertn) varieties (CO13 and PAIYUR-1), subjected to salt stress of different concentrations (0, 40, 80 and 120mM). Salinity was given as a basal dose and sampling was done in leaves on 30th Days. After Treatment (DAT). There was a marked variation in the photosynthetic rates and ribulose-1, 5-bispho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Similarly, Meneguzzo et al (1999) observed a greater increase in APX activity in a salt-sensitive cultivar than in a salt-tolerant one of wheat when exposed to NaCl stress. With the increase in salt stress, APX activity also increased in wheat (Heidari and Mesri 2008), cotton (Desingh and Kanagaraj 2007), stevia (Omran et al, 2021) and sea rocket (Amor et al, 2007) suggesting that high level of APX and salt-induced increase in APX activity could impart tolerance by detoxifying H 2 O 2 generated upon exposure of plants to saline conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Meneguzzo et al (1999) observed a greater increase in APX activity in a salt-sensitive cultivar than in a salt-tolerant one of wheat when exposed to NaCl stress. With the increase in salt stress, APX activity also increased in wheat (Heidari and Mesri 2008), cotton (Desingh and Kanagaraj 2007), stevia (Omran et al, 2021) and sea rocket (Amor et al, 2007) suggesting that high level of APX and salt-induced increase in APX activity could impart tolerance by detoxifying H 2 O 2 generated upon exposure of plants to saline conditions.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that an increase in MDA content is considered an indicator of cellular oxidative damage that is caused by several environmental stress conditions [ 49 ]. Plants can defend themselves against various environmental stresses, including WL, by upregulating cellular proline levels and lowering the MDA production to maintain cell membrane stability, detoxifying reactive oxygen species (ROS) [ 50 ], and maintaining osmotic pressure [ 51 , 52 , 53 ]. In the present study, the proline and MDA levels were significantly raised with the increasing WL duration ( Figure 3 A,B).…”
Section: Discussionmentioning
confidence: 99%
“…Osmotic stress disrupts the normal cellular activities. Proline accumulation maintains osmotic pressure in plant cell playing a significant role in the protection of cell structure in many crops [41] . The accumulation of proline in brinjal genotypes were considerably influenced by different salinity levels [29] .…”
Section: Proline Contentmentioning
confidence: 99%